Beethoven und seine Zeit - Nettl, Paul 1889-1972 (Frankfurt am Main Fischer, 1958)
Paul Nettl, a good connoisseur of composer Ludwig van Beethoven, has compiled these testimonies and, furthering the reader's understanding, commented on and explained them. The editor's own research expands the biographical details in interesting ways.The result is not only a captivating portrait of Beethoven, but also a panorama of his time and contemporaries.
Keywords: Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); 19th Century (1801-1900); Biography; Composer; Germany; Austria